Iron Availability Influences the Tolerance of Southern Ocean Phytoplankton to Warming and Elevated Irradiance - Andrew, Sarah M.; Morell, Hugh T.; Strzepek, Robert F.; Boyd, Philip W.; Ellwood, Michael J. (Frontiers in Marine Science, 2019)
The Southern Ocean is responsible for approximately 40% of oceanic carbon uptake through biological and physical processes. In the Southern Ocean, phytoplankton growth is limited by low iron (Fe) and light supply. Climate model projections for the Southern Ocean indicate that temperature, underwater irradiance and Fe supply are likely to change simultaneously in the future due to increasing anthropogenic carbon dioxide emissions. The individual effects of these environmental properties on phytoplankton physiology have been extensively researched, and culturing studies using Southern Ocean phytoplankton have shown that temperature and Fe will play a key role on setting growth under future conditions. To explore the potential responses of Southern Ocean phytoplankton to these environmental changes, we cultured the haptophyte Phaeocystis antarctica and the diatoms Chaetocerous flexuosus, Proboscia inermis and Thalassiosira antarctica under two light and iron combinations and over a range of temperatures. Our study revealed that the thermal response curves of key Southern Ocean phytoplankton are diverse, with the highest growth rates measured at 5 °C (the annual temperature range at the isolation sites is currently 1-4°C). Warming had species-specific effects on the photochemical efficiency of photosystem II (PSII; Fv/Fm), the functional absorption cross-section of PSII (σPSII), carbon:nitrogen ratio and cellular Chlorophyll a concentrations. Iron availability increased species’ ability to tolerate warmer conditions by increasing the upper limit for growth and subsequently increasing the thermal niche that each species inhabit.